2023
DOI: 10.1111/gcb.16630
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits and climate drive interspecific differences in disturbance‐induced tree mortality

Abstract: With climate change, natural disturbances such as storm or fire are reshuffled, inducing pervasive shifts in forest dynamics. To predict how it will impact forest structure and composition, it is crucial to understand how tree species differ in their sensitivity to disturbances. In this study, we investigated how functional traits and species mean climate affect their sensitivity to disturbances while controlling for tree size and stand structure. With data on 130,594 trees located on 7617 plots that were dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 112 publications
1
18
0
Order By: Relevance
“…This is particularly the case for Picea abies (L.), which is the most sensitive to bark beetles—a currently dominant biotic disturbance agent in Central Europe (Kautz et al, 2017)—and other species susceptible to biotic disturbances, such as Betula spp. (Barrere et al, 2023). Trees already under stress due to suppression are most susceptible to the influence of these processes, which may ultimately lead to tree death (Franklin et al, 1987).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is particularly the case for Picea abies (L.), which is the most sensitive to bark beetles—a currently dominant biotic disturbance agent in Central Europe (Kautz et al, 2017)—and other species susceptible to biotic disturbances, such as Betula spp. (Barrere et al, 2023). Trees already under stress due to suppression are most susceptible to the influence of these processes, which may ultimately lead to tree death (Franklin et al, 1987).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have also found an increasing probability of mortality for large trees, mainly due to senescence (Holzwarth et al, 2013;Vieilledent et al, 2010) and certain natural disturbances such as high winds (Barrere et al, 2023). Mortality due to senescence occurs in stands that have avoided natural or anthropogenic disturbances long enough for the trees to reach the end of their life span (Luo & Chen, 2011).…”
Section: The Influence Of Control Variables On Tree Mortalitymentioning
confidence: 98%
See 1 more Smart Citation
“…This included the death of three of the biggest trees (diameter > 100 cm) in the plot that died without signs of prior damage. Whether specific disturbances (e.g., fire, droughts, insect outbreaks; Barrere et al, 2023) and/or sustained changes in climatic factors (e.g., atmospheric water stress; Bauman et al, 2022) are driving these patterns remains unclear, but we found no relationship between damage-related and mortality-related AGB loss rates among periods (even when excluding Fushan and Pasoh) (Figure S5; p > .10…”
Section: Likely Factors Driving Variability In Agb Lossmentioning
confidence: 82%
“…This included the death of three of the biggest trees (diameter > 100 cm) in the plot that died without signs of prior damage. Whether specific disturbances (e.g., fire, droughts, insect outbreaks; Barrere et al, 2023) and/or sustained changes in climatic factors (e.g., atmospheric water stress; Bauman et al, 2022) are driving these patterns remains unclear, but we found no relationship between damage‐related and mortality‐related AGB loss rates among periods (even when excluding Fushan and Pasoh) (Figure S5; p > .10 in linear mixed‐effect models controlling for temporal autocorrelation within sites) suggesting that these two sources of AGB loss may either result from different drivers or operate at different timescales (i.e., lagged effects). As data collection continues, comprehensive analyses of the underlying drivers of tree mortality and damage will be possible.…”
Section: Discussionmentioning
confidence: 99%